Evaluation of catchment contributing areas and storm runoff in flat terrain subject to urbanisation - Barron, O. V.; Pollock, D.; Dawes, W. (Hydrology and earth system sciences, 2011)
Contributing Catchment Area Analysis (CCAA) is a spatial analysis technique developed and used for estimation of the hydrological connectivity of relatively flat catchments. It allows accounting for the effect of relief depressions on the catchment rainfall-runoff relationship which is not commonly considered in hydrological modelling. Analysis of distributed runoff was based on USDA runoff curves numbers (USDA, 1986), which utilised the spatial information on land cover and soil types, while CCAA was further developed to define catchment area contributing to river discharge under individual rainfall events. The method was applied to the Southern River catchment, Western Australia, showing that contributing catchment area varied from less than 20% to more than 60% of total catchment area under different rainfall and soil moisture conditions. Such variability was attributed to a compensating effect of relief depressions. CCAA was further applied to analyse the impact of urbanisation on the catchment rainfall-runoff relationship. It was demonstrated that in addition to an increase in runoff coefficient, urbanisation leads to expansion in the catchment area contributing to the river flow. This effect was more evident for the most frequent rainfall events, when an increase in contributing area was responsible for a 30–100% rise in predicted catchment runoff.